The Managing Director's Global Policy Agenda, Spring Meetings 2021 : Bolstering the Recovery, Countering the Divergence. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2021)
An unprecedented policy response and rapid progress in vaccine development have helped pull the global economy from a deep recession. But the outlook is marked by high uncertainty and great divergence. Carefully calibrated policies and stronger international cooperation are vital to safely exit the crisis. Transformative policies should aim for fast convergence toward a green, digital, and inclusive future.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet